Rencana Pengembangan Wilayah Zonasi Mangrove untuk Rehabilitasi Lahan Pasca Tsunami di Kecamatan Baitussalam Kabupaten Aceh Besar - Zainabun Zainabun; Syamsidah Djuita (Jurnal Agrista, 2011)
Plant Development of Region of Zoning Mangrove to Rehabilitate Land of Post Tsunami in District of Baitussalam Sub-Province of Aceh BesarABSTRACT. The research aim to rehabilitate land of mangrove as buffer zone in order to development of region of zoning mangrove in District of Baitussalam Sub-Province Aceh Besar. Method which is used in this research is descriptive method with technique of survey. Survey and intake of sample in field done/conducted by representative and perceive the condition of field physical. Analyzed to be land; ground sample to be taken until deepness 0 – 20 cm at the (time) of ebb sea water, each; every land; ground sample and water taken is then done/conducted by intake of coordinate point. Nature of water and land; ground in Laboratory is pH, DHL, SAR, and texture land ground. Result of Perception and research in field indicate that value of pH (6.82 – 8.02), DHL (2.40 – 7.50), SAR (1.37 – 3.00), and texture (sand, sandy loam, and sandy clay loam). Forest of Mangrove can grow and expand better as prop (buffer zone) between coastal region with continent. Development of mangrove in District of Baitussalam divided to the 3 zonings is coastal periphery zone (A) for the width of 1,091 ha (29.87%) located in countryside of Kajhu, Countryside of Cadek and Countryside of Lambada Lhok cultivated type mangrove of Rhizhospora spp. Middle zone (B) for the width of 1,289 ha (35.30%) located in countryside of Baet, Countryside of Cadek, Countryside of Kajhu, Countryside of Lambada Lhok, and Countryside of Cot Swamp cultivated type mangrove of Rhizospora mucronata, Bruguiera spp, and Ceriops spp. Hinterland zone or zone behind (C) from position go out to sea Ujong cultivated by type mangrove of Rhizospora apiculata, Mucronata Rhizopora, Avicennia spp (fires), and Nypa fructicans.